THE IMPACT OF TRANSACTION PROCESSING SYSTEMS IN MAKING OPERATIONAL DECISIONS: A CASE STUDY OF COMPUTERIZING THE EMPLOYEES AFFAIRS DEPARTMENT OF AL-BALQA APPLIED UNIVERSITY, AL-KARAK - Al-tarawneh, Wafa Atalleh (European Scientific Journal, ESJ, 2015)
The aim of this study is to determine the impact of using information system in improving and managing the decision making process of the Employees Affairs Department of Al-Balqa Applied University at Al-Karak. To achieve the goal of this study, data were obtained through an interview with the department manager. A 24 items questionnaire with five response (Likert Scale) was developed and distributed to 20 participants, representing the Employees Affairs Department. Also, I used the SPSS Package to analyze the questionnaire study data which include the means and standard deviations of the study. In addition, I used Regression analysis to test the hypotheses.